Guinea : Technical Report-Public Investment Management Assessment. (IMF Staff Country Reports; Country Report ;, 2019)
The Guinean authorities are working to reduce the country's infrastructure deficit and have provided for this effort in Guinea's 2016-20 National Economic and Social Development Plan (PNDES). Public-private partnerships (PPPs) are a mechanism used to fund major projects to be implemented. To support the process, the authorities requested technical assistance from the International Monetary Fund (IMF) to prepare a thorough assessment of the public investment management (PIM) system to supplement the Public Expenditure and Financial Accountability (PEFA) assessment conducted in March 2018. The objectives of the present mission were to evaluate PIM in Guinea using the Public Investment Management Assessment (PIMA) methodology as revised by the IMF in April 2018. This report presents public investment trends and the public investment efficiency gap, details the results of the assessment, and offers recommendations to improve PIM in Guinea.